إطار مقترح لقياس وتقييم مسببات المخاطر التشغيلية في البنوك وفقا لمتطلبات بازل: دراسة مقارنة بين البنوك التقليدية والإسلامية - أحمد، خالد محمد عثمان (جامعة الإسكندرية - كلية التجارة - قسم المحاسبة والمراجعة, 2018)
شهدت البنوك العالمية انهيارات مالية ضخمة ابان الأزمة المالية العالمية الأخيرة، ووصلت الخسائر إلى مئات مليارات الدولارات. وتم إرجاع أسباب الانهيار إلى فشل تحديد المخاطر -خاصة المخاطر التشغيلية -وغياب نظم الرقابة الداخلية الفعالة، ونتيجة لذلك اهتمت الدراسات بتحليل موضوع مخاطر البنوك. كما أدخلت لجنة بازل المخاطر التشغيلية كأحد مكونات مخاطر البنوك التي يجب قياسها، وأشارت اللجنة إلى حاجة البنوك لأكثر من 50 بليون دولار لمواجهة مخاطر التشغيل. ويتناول هذا البحث دراسة مقاربة بين البنوك التقليدية والإسلامية لقياس مسببات المخاطر التشغيلية وفقا لمتطلبات بازل 2، 1، 3، وتم إضافة مسبب الحوكمة المصرفية، وأثر ذلك على أداء البنوك، مما يخفض الخسائر المحتملة للنظام المصرفي في السعودية. وخلصت الدراسة إلى عدم وجود اختلاف بين البنوك التقليدية والبنوك الإسلامية في مسببات المخاطر التشغيلية وفي استخدام مداخل قياس المخاطر التشغيلية الكمية والوصفية، في حين يعد مسبب تغيير الآراء الفقهية في البنوك الإسلامية جوهري، مما يدعم الحوكمة متعددة الطبقات بإضافة حوكمة هيئة الرقابة الشرعية. كما توجد اختلافات في نتائج علاقة الارتباط بين السيولة والربحية ومعايير كفاية رأس المال والمؤشرات المالية وغير المالية لمخاطر التشغيل في المصارف الإسلامية وغير الإسلامية.
International banks have seen huge financial collapses during the recent global financial crisis, and losses have reached hundreds of billions of dollars. The reasons for the collapse were attributed to the failure to identify risks - especially operational risks - and the absence of effective internal control systems. Thus, previous studies focused on risks analysis. The Basel Committee also introduced operational risk as one of the core components of bank risk to be measured. The committee noted that banks need more than $ 50 billion to address operational risks only. Therefore, this study aims to measure the operational risks according to the requirements of Basel accords and whether there is a difference between conventional and Islamic banks regarding this type of risks. In addition, this study added the banking governance and its impact on the performance of banks. The study concluded that there is no difference between conventional and Islamic banks in the causes of operational risks and in the use of quantitative and qualitative operational risk approaches. Second, this study concluded that changing the jurisprudential views of Islamic banks is significant, which support multi-level governance (i.e.,Sharia supervisory board) perspective. There are also differences in the correlations among liquidity, profitability, capital adequacy and financial and non-financial indicators of operational risks in Islamic and non-Islamic banks.
Keywords: مخاطر التشغيل المصرفية -- إدارة المخاطر -- متطلبات بازل -- البنوك التقلیدیة -- البنوك الإسلامیة